2011
DOI: 10.1162/jocn.2010.21498
|View full text |Cite
|
Sign up to set email alerts
|

What Iconic Gesture Fragments Reveal about Gesture–Speech Integration: When Synchrony Is Lost, Memory Can Help

Abstract: The present series of experiments explores several issues related to gesture-speech integration and synchrony during sentence processing. To be able to more precisely manipulate gesture-speech synchrony, we used gesture fragments instead of complete gestures, thereby avoiding the usual long temporal overlap of gestures with their coexpressive speech. In a pretest, the minimal duration of an iconic gesture fragment needed to disambiguate a homonym (i.e., disambiguation point) was therefore identified. In three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 41 publications
5
53
0
Order By: Relevance
“…This was also found by Obermeier et al (2011), who used a paradigm similar to that of Holle and Gunter (2007) to reveal that when there was no temporal overlap of a word and a gesture, and participants were not explicitly asked to attend to the gestures, speech-gesture integration did not occur. However, in a subsequent study, in which the same stimuli were presented in multitalker babble noise, listeners did incorporate the gestural information with the speech signal to disambiguate the meaning of the sentence.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…This was also found by Obermeier et al (2011), who used a paradigm similar to that of Holle and Gunter (2007) to reveal that when there was no temporal overlap of a word and a gesture, and participants were not explicitly asked to attend to the gestures, speech-gesture integration did not occur. However, in a subsequent study, in which the same stimuli were presented in multitalker babble noise, listeners did incorporate the gestural information with the speech signal to disambiguate the meaning of the sentence.…”
mentioning
confidence: 57%
“…Nevertheless, most studies on lip movements as a visual enhancement of speech have used stimuli that only showed the lips or lower half of the face (e.g., Callan et al, 2003;Ross et al, 2007;Schwartz et al, 2004) to eliminate influences from the rest of the face or body. This is similar to studies in the domain of gestural enhancement of speech in noise, where most studies block the face of the speaker, the mouth, or just show the torso of the speaker, to eliminate influences from visible speech (e.g., Holle et al, 2010;Obermeier et al, 2011Obermeier et al, , 2012.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…This was recently demonstrated in two ERP experiments on the integration of iconic gestures and speech (gesture-word integration: Habets, Kita, Shao, Özyürek, & Hagoort, 2011; gesture-sentence integration : Obermeier, Holle, & Gunter, 2011). For instance, the study by Obermeier et al (2011) showed that the integration of gesture fragments and speech occurs in an automatic fashion when they were presented simultaneously. When this synchrony was lost because the gesture fragment preceded speech by 1000 msec (i.e., there was no temporal overlap between gesture fragment and lexical affiliate), effortful processing, induced via task instruction, was necessary for a successful integration.…”
Section: Introductionmentioning
confidence: 83%